The Lawyer's Guide to Writing Well : Second Edition. - Goldstein, Tom (University of California Press, 2002)
This eminently practical volume demystifies legal writing, outlines the causes and consequences of bad writing, and prescribes straightforward, easy-to-apply remedies that will make your writing readable. Complete with usage notes that address lawyers' most common errors, this well-organized book is both an invaluable tool for practicing lawyers and a sensible grounding for law students. This much-revised second edition contains a set of editing exercises (and a suggested revision key with explanations) to test your skill. This book is a definitive guide to becoming a better writer--and a bette.